Relationship between the siring capacity of beef bulls and their behaviour in multi-sire breeding groups measured by remote monitoring technologies - Vinicius A. Camargo; Edmond A. Pajor; Mathieu Pruvot; Sayeh Bayat; James C. Cross; Jennifer M. Pearson (Theriogenology, 2026)

Effects of tactile stimulation and application of umbilical antiseptic on the welfare of pre-weaned beef calves - Victor Brusin; M. Claire Windeyer; Jennifer M. Pearson; Edmond A. Pajor; Maria Camila Ceballos (Applied Animal Behaviour Science, 2025)

Magma mingling during the 1959 eruption of Kīlauea Iki, Hawaiʻi - Jennifer Marsh; Marie Edmonds; Bruce Houghton; Iris Buisman; Richard Herd (Bulletin of Volcanology, 2024)
Magma mingling and mixing are common processes at basaltic volcanoes and play a fundamental role in magma petrogenesis and eruption dynamics. Mingling occurs most commonly when hot primitive magma is introduced into cooler magma. Here, we investigate a scenario whereby cool, partially degassed lava is drained back into a conduit, where it mingles with hotter, less degassed magma. The 1959 eruption of Kīlauea Iki, Hawaiʻi involved 16 high fountaining episodes. During each episode, fountains fed a lava lake in a pit crater, which then partially drained back into the conduit during and after each episode. We infer highly crystalline tachylite inclusions and streaks in the erupted crystal-poor scoria to be the result of the recycling of this drain-back lava. The crystal phases present are dendrites of plagioclase, augite and magnetite/ilmenite, at sizes of up to 10 µm. Host sideromelane glass contains 7–8 wt% MgO and the tachylite glass (up to 0.5% by area) contains 2.5–6 wt% MgO. The vesicle population in the tachylite is depleted in the smallest size classes (< 0.5 mm) and has overall lower vesicle number densities and a higher degree of vesicle coalescence than the sideromelane component. The tachylite exhibits increasingly complex ‘stretching and folding’ mingling textures through the episodes, with discrete blocky tachylite inclusions in episodes 1 and 3 giving way to complex, folded, thin filaments of tachylite in pyroclasts erupted in episodes 15 and 16. We calculate that a lava lake crust 8–35 cm thick may have formed in the repose times between episodes, and then foundered and been entrained into the conduit during drain-back. The recycled fragments of crust would have been reheated in the conduit, inducing glass devitrification and crystallisation of pyroxene, magnetite and plagioclase dendrites and eventually undergoing ductile flow as the temperature of the fragments approached the host magma temperature. We use simple models of magma mingling to establish that stretching and folding of recycled, ductile lava could involve thinning of the clasts by up to a factor of 10 during the timescale of the eruption, consistent with observations of streaks and filaments of tachylite erupted during episodes 15 and 16, which may have undergone multiple cycles of eruption, drain-back and reheating.

The effects of a nonsteroidal anti-inflammatory drug on the behavioural and physiological parameters of beef cows and calves assisted at calving - Cecilia Lucio; M. Claire Windeyer; Edmond A. Pajor; Kathy Larson; Jennifer M. Pearson (Applied Animal Behaviour Science, 2024)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Modeling Mixed Vascular and Alzheimer’s Dementia Using Focal Subcortical Ischemic Stroke in Human ApoE4-TR:5XFAD Transgenic Mice - Eric Y. Hayden; Julia M. Huang; Malena Charreton; Stefanie M. Nunez; Jennifer N. Putman; Bruce Teter; Jason T. Lee; Andrew Welch; Sally Frautschy; Gregory Cole; Edmond Teng; Jason D. Hinman (Translational Stroke Research, 2020)

The aeroponic rhizosphere microbiome: community dynamics in early succession suggest strong selectional forces - Jennifer W. Edmonds; Joshua D. Sackett; Hunter Lomprey; Heather L. Hudson; Duane P. Moser (Antonie van Leeuwenhoek, 2020)

Experimental Detritus Manipulations Unite Surface and Cave Stream Ecosystems Along a Common Energy Gradient - Michael P. Venarsky; Jonathan P. Benstead; Alexander D. Huryn; Brock M. Huntsman; Jennifer W. Edmonds; Robert H. Findlay; J. Bruce Wallace (Ecosystems, 2018)

Organic Nitrogen Runoff in Coastal Marshes: Effects on Ecosystem Denitrification - Philip O. Lee; Julia A. Cherry; Jennifer W. Edmonds (Estuaries and Coasts, 2017)

Pollutant emissions and environmental assessment of ethyl 3-ethoxybutyrate, a potential renewable fuel - John M. E. Storey; Michael P. Bunce; Edwina M. Clarke; Jennifer W. Edmonds; Robert H. Findlay; Stephen M. C. Ritchie; Laurent Eyers; Zackery A. McMurry; James C. Smoot (Environmental Science and Pollution Research, 2016)

Spatial variation in the origin and reactivity of dissolved organic matter in Oregon-Washington coastal waters - YueHan Lu; Jennifer W. Edmonds; Youhei Yamashita; Bin Zhou; Andrea Jaegge; Matthew Baxley (Ocean Dynamics, 2015)

Denitrification in a large river: consideration of geomorphic controls on microbial activity and community structure - Corianne Tatariw; Elise L. Chapman; Ryan A. Sponseller; Behzad Mortazavi; Jennifer W. Edmonds (Ecology, 2013)
Ecological theory argues that the controls over ecosystem processes are structured hierarchically, with broader‐scale drivers acting as constraints over the interactions and dynamics at nested levels of organization. In river ecosystems, these interactions may arise from broadscale variation in channel form that directly shapes benthic habitat structure and indirectly constrains resource supply and biological activity within individual reaches. To evaluate these interactions, we identified sediment characteristics, water chemistry, and denitrifier community structure as factors influencing benthic denitrification rates in a sixth‐order river that flows through two physiographic provinces and the transitional zone between them, each with distinct geomorphological properties. We found that denitrification rates tracked spatial changes in sediment characteristics and varied seasonally with expected trends in stream primary production. Highest rates were observed during the spring and summer seasons in the physiographic province dominated by fine‐grained sediments, illustrating how large‐scale changes in river structure can constrain the location of denitrification hotspots. In addition, nirS and nirK community structure each responded differently to variation in channel form, possibly due to changes in dissolved oxygen and organic matter supply. This shift in denitrifier community structure coincident with higher rates of N removal via denitrification suggests that microbial community structure may influence biogeochemical processes.

Nitrogen Balance for the Central Arizona-Phoenix (CAP) Ecosystem - Lawrence A. Baker; Diane Hope; Ying Xu; Jennifer Edmonds; Lisa Lauver (Ecosystems, 2001)